The artist who painted a blue horse - Carle, Eric (Puffin Books, 2013)
Every child has an artist inside them, and this vibrant picture book from Eric Carle will help let it out. The artist in this book paints the world as he sees it, just like a child. There's a red crocodile, an orange elephant, a purple fox and a polka-dotted donkey. More than anything, there's imagination. Filled with some of the most magnificently colorful animals of Eric Carle's career, this tribute to the creative life celebrates the power of art.